Pengenalan Keragaman Pangan Sumber Protein pada Siswa Sekolah Dasar - Hartanti, Lucky; Ashari, Asri Mulya (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Protein is one of the important macronutrients that is needed by the body in the formation of new biomolecules, reproductive activities, transportation in the body. Protein can be obtained from animals and plants, and adequate protein intake in the body is a measure of achieving nutritional status or health indicators for both individuals and society. The aim of this community service activity (PKM) is to socialize various sources of protein that exist in the environment and can be found every day. The partners for this activity are 4th grade students of SDN No. 11 Trans Sebakul, Ledo District, Bengkayang Regency. The activity was carried out using the lecture method, followed by watching a video together regarding the importance of protein in children's growth and development. The results of the activity showed that there was an increase in the knowledge of grade 4 students regarding protein sources that are often found in daily life and how important it is to consume enough protein as needed by the body.